Deeply virtual Compton scattering in the tensor-pomeron approach - Lebiedowicz, Piotr; Nachtmann, Otto; Szczurek, Antoni (Physics letters, 2022)
The two-tensor-pomeron model proposed previously to describe low x DIS data is applied to real and virtual Compton scattering on a proton. The model includes two tensor pomerons, a soft and a hard one, and tensor reggeons. We include contributions of both transverse and longitudinal virtual photons. We show that this model gives a very good description of experimental data at small Bjorken x on deeply virtual Compton scattering (DVCS) from HERA. The reggeon exchange term is particularly relevant for describing the real-photon-proton scattering measured at lower γp energies at FNAL. We present two fits which differ somewhat in the strength of the hard pomeron contribution. In both fits we find that the interference between soft- and hard-pomeron exchange plays an important role. We find that in DVCS the soft-pomeron contribution is considerable up to Q2∼20 GeV2. Our model allows to study the transition from the small-Q2 regime, including the photoproduction (Q2=0) limit, to the large-Q2 regime, the DIS limit. We also discuss the ratio of cross sections for longitudinally and transversely polarized virtual photons in γ⁎p→γp as a function of |t| and Q2. The ratio R˜(Q2,W2,t)=(dσL/dt)/(dσT/dt) strongly increases with t. Our findings may be checked in future lepton-nucleon scattering experiments in the low-x regime, for instance, at a future Electron-Ion Collider at the BNL (EIC), and, if LHeC is realized, at the LHC.